Entrepreneurship education in TVET institutions and entrepreneurial intentions of female students in Ghana: the social support factor - Abigail Padi; Prof. Smile Dzisi; Prof. John Frank Eshun (Cogent Business & Management, 2022)
Technical and vocational education and training (TVET) is increasingly engaging the attention of governments in both developing and developed countries as a mechanism through which skilled graduates are produced for self-employment and for the labour market. This study was undertaken to examine the objective, pedagogy, and assessment procedures of the programme and its effect on entrepreneurial intentions of female students in Ghana, taking into consideration the moderating role of social support systems. The research design used was cross-sectional survey with concurrent mixed methods approach. The sample was 376. A questionnaire and an interview guide were the instruments used for data collection. The quantitative data were analysed using Hayes moderation process analysis while the qualitative data were analysed manually using open coding. The study revealed that entrepreneurship course is able to influence female students' entrepreneurial intentions. Nevertheless, this influence becomes stronger when the students are exposed to social support systems. It is recommended to management of the universities to sustain the course and also periodically review the course by ensuring that it is more practical and need-centred. The government through its agencies can also put in place effective and targeted social support structures that will help starters to take-off with ease.
Keywords: 650; Entrepreneurial intentions; Entrepreneurship education; Social Supports; Technical universities; TVET